Adams Pond Company. Grid Flat Slab Corporation - Sampson & Murdock Co. (Tufts Archival Research Center, 2005)
Page image of Adams Pond Company. Grid Flat Slab Corporation in The Boston directory for the year commencing August 1, 1925